Analisis Kinerja Keuangan Perusahaan Terhadap Harga Saham - Muhammad Iqbal Ramadhan; Laras Auditria Putri (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine the relationship between financial statement analysis consisting of Return On Assets, Current Ratio, Net Profit Margin, Earning Per Share, Current Ratio, and Leverage on stock prices. The population used in this study are all non-financial companies listed on the Stock Exchange. Indonesian securities during the 2016-2019 period, amounting to 1546 compiled from financial statements and OSIRIS. This study uses multiple linear regression for analysis techniques with STATA 14.0 software. The results showed that return on assets and Earnings Per Share had a positive and significant effect on stock prices.